STRATEGI PENDIDIK DI PONDOK PESANTREN DALAM MENINGKATKAN GENERIC LIFE SKILL(STUDI KASUS SANTRI PONDOK PESANTREN MAWARIDUSSALAM DESA TUMPATAN NIBUNG KECAMATAN BATANG KUIS) - Nurdiani, Indah Sari Ramlan Padang (Fakultas Agama Islam, 2022)
Generic Life Skills (general life skills), education is expected to be able to direct students to develop their potential to the fullest, including providing opportunities for students to improve life skills that can be used as a source of livelihood in the present and in the future. Pesantren is a forum that organizes life skills education which includes generic life skills. Pesantren as the production of ulama' with the quality of faith, Islam, knowledge and morals of students who are expected to be able to build themselves and the surrounding community. This research was conducted at the Mawaridussalam Islamic Boarding School, Tumpatan Nibung Village, Batang Kuis Regency, using qualitative research methods, with a case study approach. Data collection techniques were carried out by means of, (1) Observation, (2) Interview, and (3) Documentation. The data analysis techniques are (1) Data Reduction, (2) Data Presentation, and (3) Conclusion Drawing. The focus of this research is: (1) How are the efforts to improve the generic life skills of the Mawaridussalam Islamic Boarding School students, (2) what are the inhibiting and supporting factors in improving the generic life skills of the students at the Mawaridussalam Islamic Boarding School, and (3) what are the implications of the teacher's strategy in improving the generic life skills of students at the Mawaridussalam Islamic Boarding School. The results of this study indicate that, (1) efforts to improve the generic life skills of students can be done by providing advice and motivation to students who are obliged to take part in internal and external activities as well as holding competitions that can hone the skills of the Mawaridussalam Islamic boarding school students, (2) the inhibiting factor is students who difficult to manage, minimal facilities and infrastructure and lack of time management. The supporting factors are the family and the good performance of the management and educators at the Mawaridussalam Islamic boarding school, and (3) the implications of the educator strategy in improving generic life skills, namely an increase in the life skills of students and it can be seen that pesantren alumni have successfully entered the community with various skills they have acquired. have.